Malignant transformation of a urachal cyst—a case report and literature review - Rhudd, Adrian (J Surg Case Rep, 2018)
Urachal remnant diseases are very uncommon pathologies which are mostly benign. Rarely they can progress to a very aggressive form of Urachal cancer. The rarity of this condition has precluded large studies to help guide the diagnostic and therapeutic management of these potentially malignant lesions. In this case, a urachal cyst was discovered and conservative management was employed after a biopsy proved the lesion was benign. Unfortunately this patient represented several years later with a locally advanced urachal cancer. To date, this is the first clearly documented case of malignant transformation. The available literature surrounding these urachal cysts and cancers will be reviewed to determine if anything could have been done differently in this case and in the future should a similar case present.